THE EFFECT OF WORK DISCIPLINE AND COMPENSATION ON EMPLOYEE PRODUCTIVITY AT THE SAMSAT OFFICE INTEGRATED SERVICE UNIT (UPT) REVENUE, SOUTH MAKASSAR REGION 1 - Sahabuddin, Romansyah; Burhanuddin, Burhanuddin; Dzulfiqar, Muh. Dzaky; Darmawinata, Widhi Nugraha Sumiharja (Universitas Negeri Makassar, 2025)
Abstract: This study aims to determine the Work Discipline and Compensation on Employee Productivity at the Samsat UPT Revenue Office of South Makassar I Region. This type of research is quantitative research with an associative approach. The data collection method is carried out by distributing questionnaires. The population in this study were all employees of the Samsat UPT Revenue Office of South Makassar I Region, totaling 83 people, as well as being a sample with a sampling technique, namely saturated sampling. The data analysis technique is through the stages of validity testing, reliability testing, classical assumption testing, multiple linear regression testing, t-test, f-test, and R2 testing which are intended to test the proposed hypothesis. With data processed through the Statistical Product and Service Solution (SPSS) program. The results of this study indicate that Work Discipline and Compensation have a positive and significant effect on Employee Productivity, both partially and simultaneously. This shows that the better the level of Work Discipline and Compensation of employees at the Samsat UPT Revenue Office of South Makassar I Region, the higher the level of employee Productivity at the Samsat UPT Revenue Office of South Makassar I Region.Keywords: Work Discipline, Compensation, Employee Productivity